Association among Timing of First Visit, Antenatal Care Frequency, and Anaemia Gravidarum during the Peak Period of the COVID-19 Pandemic - Hani, Salsabilla Permata; Kuntari, Titik (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2023)
Anaemia gravidarum is a health problem that affects pregnancy outcomes. Antenatal care is an effort to screen high-risk pregnancies to provide earlier appropriate management. In 2021, the pandemic forced people to limit their activities, including antenatal care (ANC) visits. The study aimed to explain the association among the timing of the first visit, ANC frequency, and incidence of anaemia gravidarum. The case-control study used the medical record data from Puskesmas Godean 2. The subjects were 30 pregnant women with anaemia in the case group and 30 non-anaemic pregnant women in the control group. The dependent variable was the incidence of anaemia gravidarum. Other variables included age, occupation, and education of the mother, partner’s education, parity status, pregnancy spacing, nutritional status, and history of comorbidities. The chi-square and logistic regression were used to analyse the data. It was found that ANC frequency of less than four times and first visit (K1) after passing the first trimester of gestational age increased the risk of anaemia gravidarum (p-value <0.05). Efforts to increase awareness of the importance of immediate first ANC visit and frequency of ANC visits need to be made to reduce the risk of anaemia gravidarum.